LACTASE DEFICIENCY IN CHILDREN - V.A. Shcherbak; N.M. Shcherbak (Union of pediatricians of Russia, 2011)
The topic of the article is the lactase deficiency in children. The most frequent clinical manifestations - diarrhea and flatulence -are not specific to this pathology. Symptoms, typical for the majority of the diseases nosologies of the digestive system, lack of timely laboratory diagnosis, and, often, lack of pediatricians awareness about the specifics of this disease are the cause of lactase deficiency under-diagnostics. The article describes in detail the physiopathological mechanisms, clinical picture, diagnosis and dietary correction of lactase deficiency, the data concerning the prevalence of this disease are cited.Key words: lactose, lactase deficiency, children, health food.